Kota Kotamobagu (2007 - 2010) - Benny Wijana Goni; Sutrisno Mohamad; Tonny Iskandar Mondong (Transbahasa, 2024)
This study aims to analyze the conditions and developments in Kotamobagu City as a newly autonomous region from 2007 to 2010, covering economic, social, health, education, cultural, infrastructure, political, and governance sectors. The research method used is historical research, consisting of heuristics, source criticism, interpretation, and historiography. Kotamobagu, consisting of 4 sub-districts and 33 villages/kelurahan, was established based on Law No. 4 of 2007. As a new autonomous region, Kotamobagu exhibited significant development across various sectors. Infrastructure development, such as road repairs and the construction of a regional hospital (RSUD), was prioritized. Economically, the Regional Original Revenue (PAD) increased from Rp 11,191,500 in 2007 to Rp 7,000,000,000 in 2010. The Gross Regional Domestic Product (GRDP) rose from Rp 628,561 in 2007 to Rp 1,339,171 in 2010, accompanied by an increase in the Regional Budget (APBD) from Rp 100,000,000,000 in 2007 to Rp 373,073,381,501 in 2010. Developments in the social, cultural, health, and political sectors also showed significant improvements, as the centralization of governance focused on Kotamobagu City